2014
DOI: 10.1096/fj.14-254656
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology approach reveals the physiological origin of hepatic steatosis induced by liver X receptor activation

Abstract: Liver X receptor (LXR) agonists exert potent antiatherosclerotic actions but simultaneously induce excessive triglyceride (TG) accumulation in the liver. To obtain a detailed insight into the underlying mechanism of hepatic TG accumulation, we used a novel computational modeling approach called analysis of dynamic adaptations in parameter trajectories (ADAPT). We revealed that both input and output fluxes to hepatic TG content are considerably induced on LXR activation and that in the early phase of LXR agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In support of this procedure is the fact that at the beginning of a high-fat dietary intervention the excess supply of fat does, in fact, inhibit the process of DNL [106]. In accordance, Hijmans et al [70] predicted with a novel computational modelling approach that not increased DNL but the amount of FA influx determines hepatic fat load. Beyond our modelling approach, the comprehensive modelling study by Ashworth et al [48] factors in both carbohydrate and energy metabolism and shed light on the impact of insulin resistance and DNL for a zonated TG accumulation under a high-intake diet.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In support of this procedure is the fact that at the beginning of a high-fat dietary intervention the excess supply of fat does, in fact, inhibit the process of DNL [106]. In accordance, Hijmans et al [70] predicted with a novel computational modelling approach that not increased DNL but the amount of FA influx determines hepatic fat load. Beyond our modelling approach, the comprehensive modelling study by Ashworth et al [48] factors in both carbohydrate and energy metabolism and shed light on the impact of insulin resistance and DNL for a zonated TG accumulation under a high-intake diet.…”
Section: Discussionmentioning
confidence: 83%
“…Donnelly et al [33] showed already that the plasma FA supply drives mainly the hepatic TG accumulation and that its concentration is increased in NAFLD patients. In support for this, Hijmans et al [70] found by computational modelling that the hepatic influx of FAs is a major contributor to hepatic TG accumulation in early phases. But how the uptake process may shape the establishment of the zonated TG accumulation is unknown.…”
Section: Discussionmentioning
confidence: 84%
“…Yet, exposure to a positive energy balance provokes ectopic lipid accumulation in liver and muscle. As adipose-derived fatty acid flux contributes 60-80% of the hepatic lipid influx in both mice and men, subtle changes in adipose output may lead to severe hepatic consequences over time (70,71). Recently, for instance, adipose tissue lipolysis rates were found to drive hepatic glucose production (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the GCN2/mTOR/S6K1 and AMPK pathways play important roles in regulating hepatic insulin sensitivity by leucine deprivation (Xiao et al 2011); many studies have demonstrated that insulin resistance is accompanied by liver steatosis (Savage et al 2007, Kumashiro et al 2011, Birkenfeld & Shulman 2014, which suggests that GCN2 may be involved in regulating hepatic TG levels. On the other hand, GCN2 may regulate other transcription factors like C/EBPβ and LXRα (Guo & Cavener 2007), which may be involved in regulating fatty liver (Rahman et al 2007, Hijmans et al 2015, Hsieh et al 2016.…”
Section: Discussionmentioning
confidence: 99%